Gamifying Mathematics: A Hermeneutic Phenomenological Study Focused on Role-Playing Games in Linear Equations - Fardian, Dilham; Herman, Tatang; Suryadi, Didi; Prabawanto, Sufyani (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2024)
The aim of this study is to investigate how the integration of technology, particularly games, in mathematics education serves as an innovation in mathematics learning. The focus of this research is on the integration of technology in mathematics education, particularly concerning the topic of algebra, specifically linear equations in one variable, using gamification media with the assistance of RPG Maker MV application. This research employs a hermeneutic phenomenological approach to understand the subjective meanings contained in individual experiences related to the use of gamification in a learning context. A total of 39 seventh-grade students and 2 educators from a public junior high school in Luwuk were selected as subjects for this study. The research utilized both test and non-test instruments. Data analysis followed the Miles and Huberman model, involving three stages, namely data reduction, data presentation, conclusion drawing. The results showed that the integration of technology, particularly the use of gamification in mathematics education, has received a positive response from students especially in the field of students' interest, collaboration, and motivation and serves as an innovation in mathematics learning. RPG games have great potential to be used as an interactive learning tools in the classroom because they contain various interesting features that support the psychological and cognitive development of students. Researchers are recommended to design a didactic design that integrate technology, ensuring that educational practices are both engaging and effective in enhancing students' learning experiences.